Alpha fetoprotein (AFP) participates in the build up of hematopoietic cells in the early embryonic stage: an abortion case observation - Jianhong An; Yufeng Zhang; Jiao Luo; Hong Shen (BMC, 2019)
Abstract Background At the 3rd week of human embryo, some cell clumps are formed by the hyperplasia of mesenchymal cells at the germ layer of the yolk sac wall. These cell clumps are known as blood islands. The cells in the center of the blood islands further develop into primitive blood cells, such as hematopoietic stem cells. The blood island in the yolk sac further develops into the extramedullary hematopoietic tissue in 1 week at the 3rd to 4th week. Case presentation A 32-year-old pregnant woman who missed menstruation for 42 days discovered that her pregnancy required an abortion. The tissue collected after the abortion was a piece of gray-yellow and villus-like intrauterine tissue of a size of approximately 4 cm × 3 cm × 1.3 cm. The paraffin section stained with hematoxylin and eosin and observed under the light microscope showed a visible small embryo tissue in the early placental tissue. In the embryonic tissue, a large amount of extramedullary hematopoietic tissue was present, including myeloid, erythroid and megakaryocytic cells. The extramedullary hematopoietic cells were located in the blood vessels or naive liver sinus, were positive for alpha fetoprotein (AFP) and were without lymphocytes. The erythrocytes consisted of a large number of nucleated red blood cells. In addition, a neural tube and cystic structure were found. The final pathological diagnosis was as follows: Early embryonic tissue with a cystic structure formation in the embryo. After medical abortion the pregnant woman recovered well, without complications. Conclusions Our case illustrates that AFP is an important structural protein of nucleated erythrocytes and myeloid hematopoietic cells, suggesting that it may participate in the build up of nucleated erythrocytes and myeloid hematopoietic cells. Furthermore, our case suggests that nucleated red blood cells can be detected from the 42nd day of pregnancy by a peripheral blood sample from the mother.